Potensi Sport Tourism di Kecamatan Pagar Gunung Kabupaten Lahat - Nevi Elviani; Mutiara Fajar; Agung Mahendra (Journal on Education, 2023)
This study aims to determine the potential for sports tourism in Muara Dua Village, Pagar Gunung District, Lahat District. This research is a descriptive study with a qualitative approach. Data collection techniques in this study used observation, interviews, and documentation. The results of this study indicate that the potential for Sport Tourism in Pagar Gunung District, Lahat Regency is that there is Rafting, Tubing, Waterfall Hiking, Repling in Muara Dua Village and is utilized by the surrounding community for tourism sports (Sport Tourism), and is supported by several factors including : Government, Village Head, Community.